Additive, electrode plate, diaphragm, battery and electric equipment

By using the additive Ax(PO4)y(P2O7)z of a specific chemical formula in the battery, the problems of uneven carbon coating on the surface of the positive electrode material and the dissolution of iron-manganese ions are solved, which significantly improves the cycling performance and life of the battery, and is cheap.

CN119786768APending Publication Date: 2025-04-08BYD CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411731675.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The prior art is difficult to achieve uniform high-quality carbon coating on the surface of the positive electrode material, resulting in the dissolution of iron ions or manganese ions during the battery cycle, and the existing electrolyte additives are toxic and costly, and cannot take into account all aspects.

Method used

An additive Ax(PO4)y(P2O7)z of a specific chemical formula is provided for use in a battery. The dissolution of iron ions and manganese ions is significantly improved through the use of this additive and the cycling performance of the battery is improved. The additive is combined with the positive electrode active material to form an electrode sheet or separator for use in the battery to improve its performance.

Benefits of technology

By adsorbing acidic substances, the dissolution of iron and manganese ions is effectively inhibited, the cycle life and performance of the battery is improved, and the cost is low, and it does not affect the ion and electron conduction of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005160647870000121
    Figure BDA0005160647870000121
  • Figure BDA0005160647870000131
    Figure BDA0005160647870000131
Patent Text Reader

Abstract

The invention provides an additive, an electrode plate, a diaphragm, a battery and electric equipment, the chemical formula of the additive is Ax (PO4) y (P2O7) z, A comprises at least one of alkali metal and alkaline earth metal, x is greater than or equal to 8 and greater than 0, y is greater than or equal to 6 and greater than or equal to 0, z is greater than or equal to 6 and greater than or equal to 0, and y + z is greater than 0. The additive provided by the invention can significantly improve the cycle performance of the battery when applied to the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an additive, in particular to an additive, an electrode plate, a diaphragm, a battery and an electrical device, belonging to the field of secondary batteries. Background Art

[0002] The mainstream synthesis routes of positive electrode materials include solid-phase method and liquid-phase method. Usually, organic carbon sources or inorganic carbon sources such as glucose, polyethylene glycol, and carbon nanotubes are introduced to coat and modify the surface of the positive electrode particles. This not only improves the conductivity of the positive electrode material, but also reduces the dissolution of iron ions or manganese ions in the positive electrode material during the battery cycle to a certain extent.

[0003] At present, it is difficult to achieve uniform high-quality carbon coating of positive electrode materials, whether by solid phase method or liquid phase method. There are still sites with thin carbon layer or even no carbon coating on the surface of positive electrode material particles, so it is difficult to completely avoid the dissolution of iron or manganese ions. In addition, positive electrode material particles usually break during the battery cycle. The fresh interface brought by the particle breakage cannot be protected by the coating and cannot effectively inhibit the dissolution of iron or manganese ions. From the perspective of electrolyte improvement, although some electrolyte additions can reduce the dissolution of iron or manganese ions to a certain extent, there are problems such as toxicity and high price, and it is impossible to take all aspects into consideration.

[0004] Therefore, there is an urgent need to explore low-cost technical solutions that can effectively solve the dissolution of iron ions or manganese ions to promote battery development. Summary of the invention

[0005] The invention provides an additive having a specific chemical formula. When the additive is used in a battery, the dissolution of iron ions and manganese ions can be significantly improved, thereby improving the cycle performance of the battery.

[0006] The present invention also provides an electrode plate, which includes the above-mentioned additive, so that the cycle performance of the battery can be improved after being used in the battery.

[0007] The present invention also provides a separator, which comprises the above-mentioned additive, and thus can significantly improve the cycle performance of the battery after being used in the battery.

[0008] The present invention also provides a battery, which comprises the electrode plate or the diaphragm and thus has excellent performance.

[0009] The present invention also provides an electrical device, which comprises the battery and has excellent performance.

[0010] In one aspect, the present invention provides an additive, the chemical formula of which is A x (PO4) y (P2O7)z , wherein A includes at least one of an alkali metal and an alkaline earth metal, 8≥x>0, 6≥y≥0, 6≥z≥0, y+z>0.

[0011] The additive as described above, wherein the particle size D50 of the additive is less than 50 μm.

[0012] The additive as described above, wherein the specific surface area of ​​the additive is less than 30 m 2 / g.

[0013] In another aspect, the present invention provides an electrode plate, comprising the additive as described above and a positive electrode active material;

[0014] Wherein, the positive electrode active material includes at least one of lithium iron phosphate and lithium manganese iron phosphate.

[0015] The electrode plate as described above, wherein the electrode plate comprises a current collector and an active material layer;

[0016] The active material layer includes an active material and the additive;

[0017] And / or, an additive layer is disposed on at least one surface of the current collector and / or the active material layer, and the additive layer includes the additive.

[0018] The electrode plate as described above is a positive electrode plate, and the positive electrode plate comprises a positive electrode current collector and a positive electrode active material layer, and the positive electrode active material layer comprises the positive electrode active material and the additive.

[0019] In the electrode plate as described above, based on the mass of the positive electrode active material, the mass content of the additive is A, and A satisfies 0<A≤5wt%.

[0020] The electrode plate as described above, wherein the additive layer further comprises a binder;

[0021] Preferably, the additive layer comprises 0.01% to 2.5% of the additive and 1% to 5% of the binder in terms of mass content.

[0022] According to another aspect of the present invention, there is provided a diaphragm, comprising a diaphragm base layer and an additive layer covering at least a portion of the surface of the diaphragm base layer, wherein the additive layer comprises the additives described above.

[0023] In another aspect, the present invention provides a battery, comprising the electrode plate as described above and / or the separator as described above.

[0024] Another aspect of the present invention provides an electrical device including the battery as described above.

[0025] The additive provided by the present invention has a specific chemical formula and has excellent cycle performance after being used in a battery. Acidic substances are easily generated during the use of the battery, and the acidic substances will corrode the active materials, causing the dissolution of iron ions, manganese ions, etc. The additive with a specific chemical formula can effectively absorb the acidic substances during the use of the battery, preventing the acidic substances from damaging the relevant materials or structures in the battery, effectively inhibiting the dissolution of iron ions and manganese ions, and thus improving the cycle life of the battery. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] During the use of the battery, factors such as the decomposition of the electrolyte in the electrolyte will produce acidic substances. The acidic substances destroy the stability of the positive electrode active material and corrode the positive electrode active material. The dissolution of iron ions and manganese ions may occur. The dissolution of metal ions will cause the degradation of the electrode material, accelerate the aging of the battery, and reduce the cycle life of the battery.

[0028] In order to reduce the adverse effects of the dissolution of iron ions and manganese ions on the battery, the positive electrode active materials are usually coated and modified. However, the coated positive electrode active materials have the problem of thin coating layer or incomplete coating, or broken and exposed positive electrode active materials, which cannot effectively inhibit the dissolution of iron ions and manganese ions.

[0029] Inhibiting the generation of acidic substances or absorbing acidic substances through additives can block the damage of acidic substances to active materials, reduce the dissolution of iron ions and manganese ions from the source, and improve cycle stability.

[0030] In one aspect, the present invention provides an additive, the chemical formula of the additive is A x (PO4) y (P2O7) z , wherein A includes at least one of an alkali metal and an alkaline earth metal, 8≥x>0, 6≥y≥0, 6≥z≥0, y+z>0.

[0031] Specifically, A includes at least one of lithium (Li), sodium (Na), potassium (K), magnesium (Mg), and calcium (Ca).

[0032] The additive provided by the present invention can significantly improve the cycle performance of the battery after being used in the battery. The advantage of the additive compared with other additives is that the constituent elements of the additive are the same as the constituent elements of the positive electrode material, and can achieve the effect of removing acid and reducing the dissolution of manganese and iron ions. At the same time, the additive itself does not introduce new element impurities into the battery, does not affect the ion and electron conduction of the battery, and does not affect the performance of other components of the battery.

[0033] The present invention does not limit the channels for obtaining the additives. The additives conforming to the above chemical formula can be purchased through commercial channels, or the products purchased through commercial channels can be post-processed to obtain the additives.

[0034] In a specific embodiment, the post-treatment includes the following steps: adding the purchased product into an alkaline solution for alkalization treatment, and then sequentially subjecting the product to a first heating treatment, a crushing treatment, and a second heating treatment to obtain the additive of the present invention.

[0035] Among them, the relevant parameters of the post-treatment can be adjusted according to actual needs, for example, the alkaline solution includes but is not limited to at least one of ammonia water, sodium hydroxide solution, potassium hydroxide solution, lithium hydroxide solution, sodium carbonate solution, and sodium bicarbonate solution; the temperature of the alkalization treatment is 20-80°C, and the aging time is 0.5-5h; the devices for the first heating treatment and the second heating treatment include but are not limited to at least one of a vacuum oven, a blast drying oven, a box furnace, a tube furnace, a roller kiln, and a rotary kiln, and the temperature of the first heating treatment and the second heating treatment is 150-400°C, and the time is 0.5-6h; the crushing treatment includes but is not limited to grinding, ball milling, and sand milling, the rotation speed is 200-2000 rpm, and the time is 0.5-5h.

[0036] The particle size of the additive can affect the contact sites and dispersibility of the additive. In a specific embodiment, the particle size D50 of the additive is less than 50 μm.

[0037] The particle size D50 of an additive is used to characterize the particle distribution. Specifically, D50 represents the median particle size, meaning that 50% of the particles have a diameter less than or equal to this value. In other words, D50 is the median of the particle size distribution.

[0038] The present invention does not limit the detection method of the particle size D50 of the additive, and the detection can be carried out by any common detection method in the art, such as laser particle size analyzer, dynamic light scattering method, microscope image analysis and other methods.

[0039] When the particle size D50 of the additive is less than 50 μm, it can not only make the additive dispersed more evenly in the battery, but also help to increase the contact sites of the additive, more effectively neutralize acidic substances, improve the acid removal effect, and thus improve the cycle performance of the battery.

[0040] Of course, the specific surface area of ​​the additive will also have a direct impact on the acid removal ability of the additive. In one embodiment, the specific surface area of ​​the additive is less than 30 m 2 / g.

[0041] The specific surface area of ​​the additive can be detected by using common detection methods in the art, such as nitrogen adsorption method, microscope image analysis method, mercury intrusion method, etc.

[0042] When the specific surface area of ​​the additive is within the above range, it can ensure that the additive has a suitable contact area with the acidic substance, thereby increasing the absorption rate of the additive to the acidic substance, thereby improving the cycle performance of the battery.

[0043] In another aspect, the present invention provides an electrode plate, comprising the additive as described above and a positive electrode active material;

[0044] The positive electrode active material includes at least one of lithium iron phosphate and lithium manganese iron phosphate.

[0045] Since the electrode plate provided by the present invention includes the above-mentioned additives, the electrode plate has excellent cycle performance when used in a battery.

[0046] The present invention does not limit the existence form of the additive in the electrode plate. The additive can be used after being mixed with the active material, or can be used alone in the electrode plate.

[0047] In a specific embodiment, the electrode plate includes a current collector and an active material layer; the active material layer includes active materials and additives; at this time, the active materials and additives are mixed to form an active slurry under the action of a solvent and a binder, and are evenly coated on the surface of the current collector to form an active material layer.

[0048] The active material may be a positive electrode active material or a negative electrode active material.

[0049] In another specific embodiment, at least one surface of at least one of the current collector and the active material layer is provided with an additive layer, and the additive layer includes an additive.

[0050] Specifically, the additive is mixed with a solvent, a binder, etc. to form an additive slurry, and the additive slurry is evenly coated on the surface of the current collector or the surface of the active material layer to form an additive layer.

[0051] It is understandable that in the same electrode plate, the three situations of additives existing in the active material layer, the additive layer being coated on at least one side of the current collector, or the additive being coated on the surface of the active material layer may exist simultaneously or only one of them may exist.

[0052] It is understandable that the additives need to rely on a binder to improve the adhesion and stability of the additive layer, so the additive layer also includes a binder; preferably, the additive layer includes 0.01% to 2.5% additives and 1% to 5% binder by mass.

[0053] In detail, the mass content of the additive in the additive layer includes but is not limited to 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5% or a range between any two of them, and the mass content of the binder includes but is not limited to 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or a range between any two of them.

[0054] The present invention does not limit the specific type of the binder, and a common binder in the art can be selected. For example, the binder can be selected from at least one of carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyvinyl alcohol, and sodium polyacrylate.

[0055] Since the dissolution of iron ions and manganese ions mainly occurs in the positive electrode active material, when the additive is in closer contact with the positive electrode active material, the corrosion path of the acidic substance can be blocked, thereby inhibiting the dissolution of iron ions and manganese ions. In a specific embodiment, the electrode plate is a positive electrode plate, the positive electrode plate includes a positive electrode current collector and a positive electrode active material layer, and the positive electrode active material layer includes a positive electrode active material and an additive.

[0056] At this time, the positive electrode active material, additives, solvent and binder form an active slurry, which is evenly coated on the surface of the positive electrode current collector to form a positive electrode active material layer.

[0057] In order to ensure that the positive electrode active material can fully play its role and make the battery have excellent ionic conductivity and capacity, it is necessary to control the mass content of additives in the electrode sheet.

[0058] In a specific embodiment, based on the mass of the positive electrode active material, the mass content of the additive is A, and A satisfies 0<A≤5wt%.

[0059] In detail, based on the mass of the positive electrode active material, the mass content of the additive includes but is not limited to 0.1wt%, 0.5wt%, 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt%, 3.0wt%, 3.5wt%, 4.0wt%, 4.5wt%, 5.0wt% or any other range greater than 0 and less than or equal to 5wt%.

[0060] When the mass content of the additive is within the above range based on the mass of the positive electrode active material, it can not only inhibit the corrosion of the active material by the acidic substance, reduce the degradation of the active material, and further inhibit the dissolution of iron ions and manganese ions, but also give full play to the conductivity of the active material and ensure the capacity and charge and discharge efficiency of the battery.

[0061] According to another aspect of the present invention, there is provided a diaphragm, comprising a diaphragm base layer and an additive layer covering at least a portion of the surface of the diaphragm base layer, wherein the additive layer comprises the additives described above.

[0062] In detail, the common membrane base layer in this field can be selected, such as polypropylene membrane (PP), polyethylene membrane (PE), polypropylene / polyethylene double-layer composite film (PP / PE), polyimide electrospinning membrane (PI), polypropylene / polyethylene / polypropylene three-layer composite film (PP / PE / PP), cellulose non-woven fabric membrane, and one of the membranes with ceramic coating.

[0063] It can be understood that the additive layer covering at least a portion of the diaphragm base layer also includes a binder.

[0064] Since the diaphragm provided by the present invention includes an additive layer, the acidic substances generated by decomposition of the electrolyte come into contact with the additive layer in the diaphragm during the diffusion process and are absorbed by the additives in the additive layer, thereby blocking the corrosion path of the acidic substances, inhibiting the dissolution of iron ions and manganese ions, and improving the cycle performance of the battery.

[0065] In another aspect, the present invention provides a battery, comprising at least one of the electrode plate and the separator as described above.

[0066] Since the battery provided by the present invention includes at least one of the above-mentioned electrode plates and separators, it has excellent cycle performance.

[0067] Another aspect of the present invention provides an electrical device including the battery as described above.

[0068] The present invention does not limit the specific types of electrical equipment, and may include electric vehicles, mobile phones, smart homes, robots, drones, electronic cigarettes, speakers, and any other equipment that requires batteries to power them.

[0069] The electrical equipment provided by the present invention comprises the above-mentioned battery, and thus has good electrochemical performance and cycle stability.

[0070] Hereinafter, the additive, electrode plate, separator and battery provided by the present invention are introduced in detail through specific examples.

[0071] Unless otherwise specified, the reagents, materials and instruments used in the following examples are conventional reagents, conventional materials and conventional instruments in the art and can be obtained commercially. The reagents involved can also be synthesized by conventional methods in the art.

[0072] Example 1

[0073] The battery preparation process provided in this embodiment includes the following steps:

[0074] 1) Preparation of additives: Sodium pyrophosphate is added to a 10 wt% ammonia solution and aged at 25°C for 30 min for alkalization treatment, then heated to 180°C in a tube furnace and kept warm for 2 h, then heated to 280°C and kept warm for 5 h, then ball milled at 800 rpm for 2 h, then heated to 180°C and kept warm for 30 min, and after completing the post-treatment process, the additive Na4P2O7 is obtained.

[0075] 2) Preparation of electrode plates: positive electrode material LFP: binder PVDF: conductive agent CNT: additives are mixed and homogenized in a mass ratio of 100:5:5:1, the slurry is coated on a carbon-coated aluminum foil, and baked for 10 minutes to obtain a positive electrode plate.

[0076] 3) Preparation of battery: Using PP separator, graphite negative electrode, and positive electrode plate, they are rolled and assembled to obtain a 3Ah soft-pack battery.

[0077] Example 2

[0078] The battery preparation process provided in this embodiment includes the following steps:

[0079] 1) Preparation of additives: Lithium pyrophosphate was placed in a tube furnace and heated to 350°C for 5 hours, then ball-milled at 1000 rpm for 2 hours, and then heated at 200°C for 30 minutes. After the post-treatment process was completed, the additive Li4P2O7 was prepared.

[0080] 2) Preparation of electrode plates: positive electrode material LMFP: binder PVDF: conductive agent CNT: additives are mixed and homogenized in a mass ratio of 100:5:5:1, the slurry is coated on a carbon-coated aluminum foil, and baked for 10 minutes to obtain the electrode plates.

[0081] 3) Preparation of battery: The pole pieces are rolled and assembled to obtain a 3Ah soft-pack battery.

[0082] Example 3

[0083] The battery preparation process provided in this embodiment includes the following steps:

[0084] 1) Preparation of additives: sodium phosphate is added to a 10 wt % ammonia solution and aged at room temperature for 30 min for alkalization treatment, then heated to 180° C. in a tube furnace and kept warm for 2 h, then heated to 280° C. and kept warm for 5 h, then ball milled at 800 rpm for 2 h, then heated to 180° C. and kept warm for 30 min, and after completing the post-treatment process, the additive Na3PO4 is prepared.

[0085] 2) Preparation of electrode plates: positive electrode material LMFP: binder PVDF: conductive agent CNT: additives are mixed and homogenized in a mass ratio of 100:5:5:1, the slurry is coated on a carbon-coated aluminum foil, and baked for 10 minutes to obtain a positive electrode plate.

[0086] 3) Preparation of battery: Using PP separator, graphite negative electrode, and positive electrode plate, they are rolled and assembled to obtain a 3Ah soft-pack battery.

[0087] Example 4

[0088] The battery preparation process provided in this embodiment includes the following steps:

[0089] 1) Preparation of additives: Sodium phosphate and potassium pyrophosphate are added to a 10 wt % ammonia solution and aged at room temperature for 30 min for alkalization treatment, then heated to 180° C. in a tube furnace and kept warm for 2 h, then heated to 280° C. and kept warm for 5 h, then ball milled at 1000 rpm for 2 h, then heated to 200° C. and kept warm for 30 min. After completing the post-treatment process, the additive Na3PO4@K4P2O7 is prepared.

[0090] 2) Preparation of electrode plates: positive electrode material LFP: binder PVDF: conductive agent CNT: additives are mixed and homogenized in a mass ratio of 100:5:5:1, the slurry is coated on carbon-coated aluminum foil, and baked for 10 minutes to obtain the electrode plates.

[0091] 3) Preparation of battery: The pole pieces are rolled and assembled to obtain a 3Ah soft-pack battery.

[0092] Example 5

[0093] The battery preparation method provided in this embodiment is basically the same as that in embodiment 1, except that:

[0094] The additive provided in this embodiment is lithium phosphate Li3PO4.

[0095] Example 6

[0096] The battery preparation method provided in this embodiment is basically the same as that in embodiment 1, except that:

[0097] The additive provided in this embodiment is commercially available lithium pyrophosphate Li4P2O7.

[0098] Example 7

[0099] The battery preparation method provided in this embodiment is basically the same as that in embodiment 1, except that:

[0100] The additive provided in this embodiment is commercially available Na3PO4.

[0101] Example 8

[0102] The battery preparation method provided in this embodiment is basically the same as that in embodiment 1, except that:

[0103] 2) Preparation of electrode plates: negative electrode material graphite: binder CMC: conductive agent carbon black: additives are mixed and homogenized in a mass ratio of 100:5:5:1, the slurry is coated on carbon-coated aluminum foil, and baked for 10 minutes to obtain the negative electrode plate.

[0104] 3) Preparation of battery: Using PP separator, the above negative electrode plate and the positive electrode plate LFP are rolled and assembled to obtain a 3Ah soft-pack battery.

[0105] Example 9

[0106] The battery preparation process provided in this embodiment includes the following steps:

[0107] 1) Preparation of additives: Sodium pyrophosphate is added to a 10 wt% ammonia solution and aged at 25° C. for 30 min for alkalization treatment, then heated to 180° C. in a tube furnace and kept warm for 2 h, then heated to 280° C. and kept warm for 5 h, then ball milled at 800 rpm for 2 h, then heated to 180° C. and kept warm for 30 min, and after the post-treatment process, the additive is obtained.

[0108] 2) Preparation of diaphragm: The additive is coated on the PP diaphragm, that is, the additive is made into a slurry and then sprayed on the diaphragm to obtain the diaphragm.

[0109] 3) Preparation of battery: Using the above-mentioned separator, graphite negative electrode, and positive electrode sheet LFP, they were rolled and assembled to obtain a 3Ah soft-pack battery.

[0110] Wherein, based on the mass of the positive electrode active material, the mass content of the additive is 1 wt %.

[0111] Example 10

[0112] The battery preparation process provided in this embodiment includes the following steps:

[0113] 1) Preparation of additives: Sodium pyrophosphate is added to a 10 wt% ammonia solution and aged at 25° C. for 30 min for alkalization treatment, then heated to 180° C. in a tube furnace and kept warm for 2 h, then heated to 280° C. and kept warm for 5 h, then ball milled at 800 rpm for 2 h, then heated to 180° C. and kept warm for 30 min, and after the post-treatment process, the additive is obtained.

[0114] 2) Preparation of electrode plates: The additives are homogenized and extruded and sprayed on the surface of the aluminum foil, and then the surface slurry is coated: positive electrode material LFP: binder PVDF: conductive agent CNT in a ratio of 100:5:5 and baked for 10 minutes to obtain the positive electrode plate.

[0115] 3) Preparation of battery: Using PP separator, graphite negative electrode, and positive electrode plate, they are rolled and assembled to obtain a 3Ah soft-pack battery.

[0116] Wherein, based on the mass of the positive electrode active material, the mass content of the additive is 1 wt %.

[0117] Comparative Example 1

[0118] The preparation method of the battery provided in this comparative example is basically the same as that in Example 1, except that:

[0119] The active material layer of the positive electrode sheet does not include the additive of Example 1.

[0120] Comparative Example 2

[0121] The preparation method of the battery provided in this comparative example is basically the same as that in Example 2, except that:

[0122] The active material layer of the positive electrode sheet does not include the additive of Example 2.

[0123] Comparative Example 3

[0124] The preparation method of the battery provided in this comparative example is basically the same as that of Example 3, except that:

[0125] The active material layer of the positive electrode sheet does not include the additive of Example 3.

[0126] Comparative Example 4

[0127] The preparation method of the battery provided in this comparative example is basically the same as that of Example 4, except that:

[0128] The active material layer of the positive electrode sheet does not include the additive of Example 4.

[0129] Comparative Example 5

[0130] The preparation method of the battery provided in this comparative example is basically the same as that of Example 6, except that:

[0131] The active material layer of the positive electrode sheet does not include the additive of Example 6.

[0132] Test Case

[0133] 1. Testing of physical parameters of additives

[0134] The particle size D50 and specific surface area of ​​the additives provided in all embodiments were measured using a laser particle size instrument in accordance with GB / T 19077-2016. The specific values ​​are shown in Table 1.

[0135] Table 1

[0136] Serial number Particle size D50(μm) <![CDATA[Specific surface area (m 2 / g)]]> Example 1 0.80 15.4 Example 2 0.71 20.1 Example 3 0.72 19.7 Example 4 0.83 21.1 Example 5 12.8 0.97 Example 6 14.6 0.56 Example 7 15.7 0.8 Example 8 0.80 15.4 Example 9 0.80 15.4 Example 10 0.80 15.4

[0137] 2. Ion dissolution test

[0138] (1) The additives provided in all embodiments were tested by EPA 6010D-2018 inductively coupled plasma atomic emission spectrometry. 0.01 g, 0.03 g, and 0.05 g of the additives were mixed with 1 g of lithium iron phosphate or lithium manganese iron phosphate, respectively, and placed in EC:DMC=7:3, 1M lithium hexafluorophosphate electrolyte and soaked at 45°C for 20 days. The electrolyte after soaking was sent to ICP to detect the amount of iron ions and manganese ions dissolved in lithium iron phosphate, as shown in Table 2. A control group 1 and a control group 2 were set at the same time, wherein control group 1 was 1 g of lithium iron phosphate placed in EC:DMC=7:3, 1M lithium hexafluorophosphate electrolyte and soaked at 45°C for 20 days. :DMC=7:3, 1M lithium hexafluorophosphate electrolyte was soaked at 45℃ for 20 days, and the electrolyte after soaking was sent to ICP to detect the dissolution of iron ions and manganese ions. The dissolution amount of control group 1 was measured to be 120ppm; control group 2 was 1g lithium iron manganese phosphate put into EC:DMC=7:3, 1M lithium hexafluorophosphate electrolyte and soaked at 45℃ for 20 days. The electrolyte after soaking was sent to ICP to detect the iron ions and manganese ions in the lithium iron manganese phosphate. The iron ion dissolution amount of control group 2 was measured to be 68ppm, and the manganese ion dissolution amount of control group 2 was 96ppm.

[0139] Table 2

[0140]

[0141] According to Table 2 and the results of control group 1 and control group 2, the additive provided by the present invention has a good inhibitory effect on the dissolution of iron ions and manganese ions. Although the inhibitory effect of the additives provided in Examples 5 to 7 is poorer than that of other examples, it is still better than the inhibitory effect of control group 1 without adding additives.

[0142] (2) The batteries provided in all the embodiments and comparative examples were tested. After 500 cycles at 1.0C rate at 45°C, the batteries were disassembled and the iron ion content and manganese ion content in the negative electrode sheets were tested. The specific test results are shown in Table 3.

[0143] Detection of cycle capacity retention rate: 45℃, 1.0C, constant current and constant voltage charge and discharge, charge to 3.65V, cut off 0.02C, constant current discharge, put into 2.5V, at 45℃, charge to 3.65V at a charge rate of 1C, cut off 0.02C, constant current discharge, put into 2.5V, repeat this charge and discharge cycle 500 times, measure the discharge capacity Q1 at the first cycle and the discharge capacity Q at the 500th cycle 500 .

[0144] Capacity retention rate Q = Q 500 / Q1*100%.

[0145] Table 3

[0146]

[0147] According to Table 3, after the additives provided in Examples 1-10 of the present invention are applied to the battery, the dissolution amount of iron ions is not higher than 55ppm, the dissolution amount of manganese ions is not higher than 26ppm, and the battery cycle capacity retention rate is not less than 92.52%, which is significantly better than the battery of Comparative Examples 1-5 without using additives. It can be seen that the technical solution provided by the present invention can significantly inhibit the dissolution of iron ions and manganese ions and ensure the cycle performance of the battery.

[0148] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. An additive, characterized in that: The chemical formula of the additive is A x (PO4) y (P2O7) z , wherein A includes at least one of an alkali metal and an alkaline earth metal, 8≥x>0, 6≥y≥0, 6≥z≥0, y+z>0.

2. The additive according to claim 1, characterized in that The particle size D50 of the additive is less than 50 μm.

3. The additive according to claim 1 or 2, characterized in that The specific surface area of ​​the additive is less than 30m 2 / g.

4. An electrode plate, characterized in that: Comprising the additive according to any one of claims 1 to 3 and a positive electrode active material; Wherein, the positive electrode active material includes at least one of lithium iron phosphate and lithium manganese iron phosphate.

5. The electrode plate according to claim 4, characterized in that: The electrode plate comprises a current collector and an active material layer; The active material layer includes an active material and the additive; And / or, an additive layer is disposed on at least one surface of the current collector and / or the active material layer, and the additive layer includes the additive.

6. The electrode plate according to claim 5, characterized in that: The electrode plate is a positive electrode plate, and the positive electrode plate includes a positive electrode current collector and a positive electrode active material layer, and the positive electrode active material layer includes the positive electrode active material and the additive.

7. The electrode plate according to any one of claims 4 to 6, characterized in that: The mass content of the additive is A based on the mass of the positive electrode active material, and A satisfies 0<A≤5wt%.

8. The electrode plate according to claim 5, characterized in that: The additive layer also includes a binder; Preferably, the additive layer comprises 0.01% to 2.5% of the additive and 1% to 5% of the binder in terms of mass content.

9. A diaphragm, characterized in that: The diaphragm comprises a diaphragm base layer and an additive layer covering at least a portion of the surface of the diaphragm base layer, wherein the additive layer comprises the additive according to any one of claims 1 to 3.

10. A battery, characterized in that: It comprises the electrode plate described in any one of claims 4 to 7 and / or the diaphragm described in claim 9.

11. An electrical device, characterized in that: Comprising the battery as claimed in claim 10.

Citation Information

Patent Citations

  • Nonaqueous electrolyte lithium ion secondary battery

    CN102549819A

  • Nonaqueous electrolyte secondary battery and method of manufacturing the same

    CN106356563A

  • Lithium ion battery

    CN110970621A

  • High-voltage electrolyte suitable for nickel lithium manganate material

    CN115395101A

  • Nonaqueous electrolyte secondary battery

    CN115398697A